Modelo de producción industrial para la elaboración de abono orgánico a partir de los residuos generados en la zona urbana de la ciudad de Neiva. (2020)
The process of making organic compost in Colombia is mostly artisanal and through this project an industrial elaboration model of these fertilizers is proposed, thus avoiding the generation of leachate and obtaining the product in the shortest possible time without losing its characteristics.